A Review: Classification, Chemical Compositions and Antioxidant Properties of Red, Brown and Green Macroalgae - Nguyen, Ngoc Trang Thuy; Tran, Thanh Men (Marine Science Department Diponegoro University, 2024)
In human body, free radicals cause oxidative stress which is reported to be the main reason of many life style human diseases. This stress induced by the imbalance of antioxidants and oxidants. Many deadly diseases induced by oxidative stress as it forms the root cause of several degenerative changes in the cells and tissues. Nucleic acids, lipids and proteins in our body are demaged by this stress, made changes to cellular functions and lead to apoptosis or necrosis. Antioxidants have an important role in protection human body from oxidative damages and prevention of many chronic diseases, for example, diabetes, cardiovascular disease, aging, even diseases related to the nervous system. Currently, the exploration of natural antioxidants is trends in the pharmaceutical industries because synthetic antioxidants are reported to cause major side effects. Antioxidants of natural origin are considered safe and highly effective. These substances are abundant in many medicinal herbs including algae, fungi, plants and animals. Among them, seaweed is believed to be a potential source of medicinal herbs capable of synthesizing compounds with good biological activity. Off these, macroalgae, including red, brown, and green macroalgae, are considered a natural source of antioxidant components that can provide a valuable contribution to the innovation of pharmaceutical and industrial fields. Since algal products' antioxidant properties and nutritional benefits have been increasingly recognized, their properties as antioxidants require further investigative studies. This review provides information on various aspects of antioxidants, including algal sources containing antioxidants, the chemical composition of macroalgae, and antioxidant components, as well as their benefits to human health.